2016
DOI: 10.1155/2016/9063087
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluromycin, a Novel Hyaluronidase Inhibitor, Attenuates Pancreatic Cancer Cell Migration and Proliferation

Abstract: Pancreatic ductal adenocarcinoma (PDAC) is characterized by accelerated production and degradation of hyaluronan (HA), a major component of extracellular matrix involved in the malignant phenotype of cancer. In particular, increased hyaluronidase (HYAL) activity plays a critical role in cancer progression, at least in part, by producing low-molecular-weight- (LMW-) HA or small fragments of HA, suggesting HYAL as a target for cancer treatment. Hyaluromycin, a new member of the rubromycin family of antibiotics, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Glycyrrhizin has also been used as a drug delivery carrier for cancer therapy [35]. We also showed that a novel hyaluronidase inhibitor, Hyaluromycin, inhibits proliferation and migration of PDAC cells [36]. These promising agents should be tested for the selective treatment of HAMP+ PDAC in preclinical and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Glycyrrhizin has also been used as a drug delivery carrier for cancer therapy [35]. We also showed that a novel hyaluronidase inhibitor, Hyaluromycin, inhibits proliferation and migration of PDAC cells [36]. These promising agents should be tested for the selective treatment of HAMP+ PDAC in preclinical and clinical studies.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies using PEGPH20 have demonstrated that depletion or reduction of hyaluronic acid results in improved tumor perfusion and thus improved delivery of cytotoxic therapy in PDAC mouse models [ 10 , 126 , 127 ]. Moreover, its importance is highlighted by its ability to promote cell survival, proliferation, and invasion via binding to CD44 [ 128 , 129 , 130 , 131 , 132 ] and the receptor for hyaluronic acid-mediated motility (RHAMM) [ 133 ]. In addition to PEGPH20, HA may also be targeted using angiotensin inhibitors, which have been shown to reduce stromal HA and collagen production [ 134 ].…”
Section: Proteoglycans and Glycoproteinsmentioning
confidence: 99%
“…It was found that neomenthol modulates the enzyme activity up to 10% in EAC cells of mice. A higher expression of hyaluronidase in breast, prostate, bladder, pancreas cancer cells has been reported; however, no report is available on the modulation of hyaluronidase activity in EAC cells, which may either be due to lesser hyaluronidase expression or feeble interaction of hyaluronidase with natural products [61] , [62] , [63] . Therefore, neomenthol did not significantly inhibit the hyaluronidase activity in EAC cells of mice.…”
Section: Resultsmentioning
confidence: 98%